Rancang Bangun Sistem Pengelolaan Administrasi Kemahasiswaan - Hidayat Chandra; Tajuddin Abdillah; Roviana H. Dai (Gorontalo State University, 2021)
This research is motivated by the obstacles that are often experienced by student administration at the Faculty of Engineering, State University of Gorontalo. The obstacles that are often experienced, including the management of student administration letters, have not been optimal yet, there is no information regarding the process of the management of letters to students, and the making of reports is running slowly. The method used in this research is the prototype method. The research finding is in the form of a student administration management system that can facilitate the process of managing and making student administration reports. In addition, this student administration management system makes the students can easily find out the progress of student administration management in the Faculty of Engineering, State University of Gorontalo